Serious life events and associated PTSD in Gambian girls exposed to female genital cutting - Heir, Trond; Bendiksen, Bothild; Minteh, Fabakary; Kuye, Rex A.; Lien, Inger-Lise (Frontiers in Public Health, 2023)
Introduction Poor mental health, such as post-traumatic stress disorder (PTSD), has been reported after female genital cutting (FGC). However, data documenting adverse consequences of FGC have insufficiently considered confounding factors, such as other traumatising events. Here, we examined the extent to which FGC versus other serious life events disturbed Gambian girls subjected to FGC. We additionally assessed the prevalence of PTSD and the extent to which it was attributed to FGC versus other serious life events. Methods We conducted a cross-sectional study with a community-based sample of 12 years-old Gambian girls who had been subjected to FGC (N = 125). Using structured interviews, we assessed serious life events and probable PTSD related to the event that the girls cited as bothering them the most. Results Most of the girls reported several serious life events in addition to FGC, such as witnessing violence, experiencing violence or assaults, death of a close relative, and being exposed to natural disasters or serious accidents, for an average 4.5 events per girl. Around one-sixth of the girls (16.8%) stated that FGC was the event that currently bothered them the most, whereas the majority (75.2%) emphasised other experiences. The girls who said they were most troubled by other events reported more impaired daily functioning than those most bothered by FGC. Overall, we found a prevalence of probable PTSD of 19.2%. Of 24 PTSD cases, one was attributed to the experience of FGC, and the remaining 23 were attributed to other events. Conclusion Our findings indicate that FGC is less important than other serious life events in explaining high rates of PTSD in Gambian girls. Associations established in the field between FGC and adverse mental health must be interpreted with caution because girls who have undergone FGC may be severely exposed to other traumatising events.